2022
DOI: 10.3390/antibiotics11070981
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Antimicrobial Exposure: Impact on Clostridioides difficile Colonization in Infants

Abstract: The relationship between antibiotic use and Clostridioides difficile (C. difficile) has been well established in adults and older children but remains unclear and is yet to be fully examined in infant populations. This study aimed to determine the separate and cumulative impact from antibiotics and household cleaning products on C. difficile colonization in infants. This study included 1429 infants at 3–4 months of age and 1728 infants at 12 months of age from the Canadian Healthy Infant Longitudinal Developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…C-section birth increases the susceptibility to early childhood asthma26 which is suggested to be due to an underdeveloped gut microbiota composition in the infant 27 28. Antibiotic use during pregnancy29 and early childhood30 are also known to disrupt the composition of the gut microbiota in children. We found that antibiotic use in early childhood appears to have a larger impact on asthma disease programming than fetal exposure: in our cohort of children with asthma, maternal antibiotic use during pregnancy was associated with a slight increase in the risk of partly controlled asthma (aRR: 1.11); however, we saw a higher likelihood of uncontrolled asthma in children who had antibiotics dispensed between 30 days of life and prior to their asthma diagnosis (aRR: 1.32).…”
Section: Discussionmentioning
confidence: 99%
“…C-section birth increases the susceptibility to early childhood asthma26 which is suggested to be due to an underdeveloped gut microbiota composition in the infant 27 28. Antibiotic use during pregnancy29 and early childhood30 are also known to disrupt the composition of the gut microbiota in children. We found that antibiotic use in early childhood appears to have a larger impact on asthma disease programming than fetal exposure: in our cohort of children with asthma, maternal antibiotic use during pregnancy was associated with a slight increase in the risk of partly controlled asthma (aRR: 1.11); however, we saw a higher likelihood of uncontrolled asthma in children who had antibiotics dispensed between 30 days of life and prior to their asthma diagnosis (aRR: 1.32).…”
Section: Discussionmentioning
confidence: 99%